RAINFALL MAPS FOR THE SUITABILITY OF SETTLEMENT AREA IN BOGOR RAYA - Niken Anissa Putri; Adi Wibowo (EnviroScienteae, 2023)
The rainfall map can be used as a reference for settlements in Bogor Raya while still paying attention to the surrounding environment so that no damage occurs. The research aims to identify the classification and score factor average rain intensity. Second, to make rainfall maps in Bogor Raya based on high and low rainfall intensity. Third, to identify the potential suitability of Resident Areas in Bogor Raya regarding rainfall variables. The method used is the overlay between the Meteorological, Climatological, and Geophysical Agency data and the Geospatial Information Agency. The annual average rainfall data for Bogor Raya is based on the Meteorological, Climatological, and Geophysical Agency, and the Bogor Raya administration is based on Geospatial Information Agency. Analyzing the suitability of settlement locations in Bogor Raya used SMCA as the primary method. The variables refer to site characteristics and land suitability, such as rainfall. The results show that the average rainfall map has three classes, such low (1,000 – 2,000 mm/year), middle (2,000 – 3,000 mm/year), and high (3,000 – 4,000 mm/year) in Bogor Raya. The results show that potential suitability for Residential Areas in Bogor Raya has high suitability potential because high rainfall levels dominate these areas (2.000 – 4.000 mm/year).